Contribution to Understanding the Occurrence of Extractives in Red Heart of Beech - Viljem Vek; Primož Oven; Ida Poljanšek; Thomas Ters (BioResources, 2014)
Common beech (Fagus sylvatica) is one of the deciduous tree species characterized by the formation of a discolored red heart in the central part of the stem. The aim of this work was to review data in existing literature and to present original results on the extractives present in sapwood and the red heart of beech. Samples of sapwood and red heart were taken from freshly felled beech trees and extracted with a speed extractor. The content of lipophilic and hydrophilic extractives was determined gravimetrically and further evaluated by gas chromatography. The beech wood contained, on average, 1.04% lipophilic and 3.71% hydrophilic extractives. Even though the gravimetrically determined content of lipophilic extractives was comparable in the sapwood and the red heart, saturated fatty acids, fatty alcohols, and free sterols were dominant in the red heart. Sapwood contained a larger amount of total hydrophilic extractives. Mono- and oligosaccharides, sugar acids and alcohols, carboxylic acids, simple phenols, and flavonoids were identified as the prevailing hydrophilic solubles in sapwood, whereas the concentration of sugar alcohols was higher in the red heart. The composition and character of the extractives in the wood of red-hearted beech should be considered the relevant technological factor.